2015
DOI: 10.1108/cr-12-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

Chinese M & A in Europe

Abstract: Purpose – This paper aims to examine the global competitiveness of an emerging market multinational (EMM) from China through the case of a major European acquisition, in Italy, in the heavy construction industry. Country- and firm-specific factors are considered. Horizontal integration in this oligopolistic industry changes the industry dynamics, with significant implications for its players. Design/methodology/approach – The paper follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The study found three key factors: the ability to identify strategic assets, the ability to assimilate and integrate the acquired assets, and the ability to utilize those assets to enhance business performance. Later, Spigarelli, Alon, and Mucelli (2015) noted some additional factors at the firm level. These included integration in R&D, marketing, and sales; the development of communication and trust; the exploitation of the Chinese market as a source of demand; and moving selected production lines to the Chinese market.…”
Section: Factors Affecting the Success And Failure Of Chinese Ofdimentioning
confidence: 99%
“…The study found three key factors: the ability to identify strategic assets, the ability to assimilate and integrate the acquired assets, and the ability to utilize those assets to enhance business performance. Later, Spigarelli, Alon, and Mucelli (2015) noted some additional factors at the firm level. These included integration in R&D, marketing, and sales; the development of communication and trust; the exploitation of the Chinese market as a source of demand; and moving selected production lines to the Chinese market.…”
Section: Factors Affecting the Success And Failure Of Chinese Ofdimentioning
confidence: 99%
“…The extent to which the ICF increases the recognition of Chinese brands remains almost completely uninvestigated. Except for a case study by 40 IJOEM 14,1 Spigarelli et al (2015) about the acquisition of CIFA by Zoomlion, which reveals that the two companies established a joint brand after the closure of the acquisition and now distribute products under this common label in the Chinese market, no articles that address this issue have been identified.…”
Section: Research Advancements and New Impulses Regarding The Outcomes Or Consequences Of The Icfmentioning
confidence: 99%
“…Through better understanding, it becomes possible to develop an efficient MAS for decentralised companies operating in the industry. Studies show several industry-specific CSFs that executives in the construction sector need to be aware of in order to gain a competitive edge (Kärnä, 2009;Spigarelli, Alon & Mucelli, 2015;Yang, Yeung, Chan, Chiang examined on project level as well as on organisational or on stakeholder level. For instance, construction companies operate in a distinctive manner, since they need to handle various separate projects at the same time.…”
Section: Csfs In the Construction Industrymentioning
confidence: 99%
“…Studies illustrate the industry-specific success factors that executives in the construction sector need to focus on in order to gain a competitive edge (Kärnä, 2009;Spigarelli et al, 2015;Yang et al, 2010). The empirical evidence shows that CSFs in the construction industry differ from one country to another.…”
Section: Summary: Identification Of Research Gapmentioning
confidence: 99%
See 1 more Smart Citation